Asbāb al-Nuzūl Al-Qur'an and its Relevance to Islamic Education - Nasution, Muhammad Roihan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
-This research aims to describe Asbāb al-Nuzūl and its relevance to Islamic education. This research is qualitative with a type of literature review. As a literature research, research data is in the form of cutting-edge journal research articles related to Asbāb al-Nuzūl and Islamic education. The data source is obtained from Sinta-accredited e-journals  and reputable e-journals. The data collection technique uses documentation. The data analysis uses content analysis. The results of the study mention three main points between Asbāb al-Nuzūl and Islamic education, namely, the relevance of Asbāb al-Nuzūl, the reading of progressive verses for Islamic education based on Asbāb al-Nuzūl, and the pedagogical solution of the Qur'an for contemporary Islamic education. Understanding Asbāb al-Nuzūl and studying progressive verses is an important part of relevant and contextual Islamic education. From there, one can explore the pedagogical principles of the Qur'an that not only convey knowledge, but also shape character and social awareness. The solution offered by the Qur'an is very appropriate to improve contemporary Islamic education so that it remains grounded in divine values as well as adaptive to the challenges of the times.